2018
DOI: 10.1007/s00253-018-9453-z
|View full text |Cite
|
Sign up to set email alerts
|

Rubber oxygenases

Abstract: Natural rubber (NR), poly(cis-1,4-isoprene), is used in an industrial scale for more than 100 years. Most of the NR-derived materials are released to the environment as waste or by abrasion of small particles from our tires. Furthermore, compounds with isoprene units in their molecular structures are part of many biomolecules such as terpenoids and carotenoids. Therefore, it is not surprising that NR-degrading bacteria are widespread in nature. NR has one carbon-carbon double bond per isoprene unit and this fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 78 publications
0
45
0
Order By: Relevance
“…Mcl-PHA C 6 -HHx C 8 -HO C 10 -HD C 12 Material T2). Then, different molar concentrations of Tris-HCl buffer in the range from 0.025 to 0.5 M were investigated at the optimum incubation temperature 30 • C (Supplemental Material T3).…”
Section: Average Volumetric Rate Of In Vivo Depolymerization Of Intramentioning
confidence: 99%
See 2 more Smart Citations
“…Mcl-PHA C 6 -HHx C 8 -HO C 10 -HD C 12 Material T2). Then, different molar concentrations of Tris-HCl buffer in the range from 0.025 to 0.5 M were investigated at the optimum incubation temperature 30 • C (Supplemental Material T3).…”
Section: Average Volumetric Rate Of In Vivo Depolymerization Of Intramentioning
confidence: 99%
“…Mcl-PHA C 6 -HHx C 8 -HO C 10 -HD C 12 to other factors such as temperature. This also opens up the possibility of adopting the aforementioned system for chiral molecules production in a cell-free biology process [51].…”
Section: Average Volumetric Rate Of In Vivo Depolymerization Of Intramentioning
confidence: 99%
See 1 more Smart Citation
“…The Gram-negative bacterium S. cummioxidans 35Y lacks the lcp, but is able to degrade rubber due to the action of the Rubber oxygenase A (RoxA) [10]. Myxococcus fulvus, Haliangium ochraceum, Corallococcus coralloides, all gamma-proteobacteria, and also R. gummiphilus NS21 have the gene roxA [28,29]. Recent studies demonstrated that RoxA from R. gummiphilus is able to cleave polyisoprene to the C15 oligoisoprenoid [28].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a novel type of rubber oxygenase was reported in S. cummioxidans 35Y (RoxB) [30] and R. gummiphilus NS21 (LatA) [11,31]. Comparisons of the amino acid sequence and other properties showed RoxB and LatA are homologues, but RoxA is not a homologue of RoxB/LatA [28][29][30]. Two species of Gordonia (G. westfalica and G. polyisoprenivorans) have been associated to rubber degradation; both have the Lcp and are able to use this substrate as sole carbon source [12,13].…”
Section: Introductionmentioning
confidence: 99%